Correlation and capability of using site inspection data and small specimen creep testing for a service-exposed CrMoV pipe section. (4th March 2019) - Cacciapuoti, B.; Morris, Andy; Sun, Wei; McCartney, David Graham; Hulance, Jeff
ABSTRACT: This paper presents for the first time an investigation on the creep damage evolution of an ex-service CrMoV pipe section through impression creep test (ICT) and metallurgical inspection data. The study emphasises the importance of correlating the operating conditions (temperature and stress) of power plant components with the results from metallurgical examinations and small specimen creep tests. The paper seeks for a correlation among micro- and macro-hardness measurements, surface replicas data and minimum creep strain rates (obtained by ICTs) of the parent material of the pipe section. Also, optical and scanning electron microscope (SEM) micrographs have been used to assess possible metallurgical differences through the thickness of the pipe section. This investigation shows how miniature creep test specimen data could be practically used in a holistic approach for the evaluation of life consumption of power plant components and concludes that the studied parent material could have been retired from service too early.